PENGARUH KOMITE AUDIT, AUDIT INTERNAL, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN TERDAFTAR DI BEI PERIODE 2020-2024 - Novi Kirana; Zulmita; karsam (Universitas La Tansa Mashiro, 2025)
This study examines the influence of the audit committee, internal audit, and independent board of commissioners on financial performance in the banking sector. Utilizing a quantitative design, secondary data from the annual reports of 26 companies (2020 to 2024), yielding 130 data points, were analyzed using multiple linear regression. The results indicate that the audit committee, internal audit, and the independent board of commissioners all significantly influence financial performance. Collectively, these three variables explain 39.4% of the variation.